T cell specific deletion of Casitas B lineage lymphoma-b reduces atherosclerosis, but increases plaque T cell infiltration and systemic T cell activation - Vos, Winnie G.; van Os, Bram W.; den Toom, Myrthe; Beckers, Linda; van Roomen, Cindy P.A.A.; van Tiel, Claudia M.; Mohapatra, Bhopal C.; Band, Hamid; Nitz, Katrin; Weber, Christian; Atzler, Dorothee; de Winther, Menno P.J.; et al. (Frontiers in Immunology, 2024)
Atherosclerosis is a lipid-driven inflammatory disease of the arterial wall, and the underlying cause of the majority of cardiovascular diseases. Recent advances in high-parametric immunophenotyping of immune cells indicate that T cells constitute the major leukocyte population in the atherosclerotic plaque. The E3 ubiquitin ligase Casitas B-lymphoma proto-oncogene-B (CBL-B) is a critical intracellular regulator that sets the threshold for T cell activation, making CBL-B a potential therapeutic target to modulate inflammation in atherosclerosis. We previously demonstrated that complete knock-out of CBL-B aggravated atherosclerosis in Apoe -/-mice, which was attributed to increased macrophage recruitment and increased CD8 + T cell activation in the plaque. To further study the T cell specific role of CBL-B in atherosclerosis, Apoe -/-CD4 cre Cblb fl/fl (CBL-B CD4cre Cblb cKO ) mice and Cblb wild-type Apoe -/-CD4 WT Cblb fl/fl littermates (CBL-B WT Cbl-bbl-b fl/fl ) were fed a high cholesterol diet for ten weeks. CBL-B CD4cre Cbl-b cKO mice had smaller atherosclerotic lesions in the aortic arch and root compared to CBL-B WT Cbl-b fl/fl , and a substantial increase in CD3 + T cells in the plaque. Collagen content in the plaque was decreased, while other plaque characteristics including plaque necrotic core, macrophage content, and smooth muscle cell content, remained were unchanged. Mice lacking T cell CBL-B had a 1.4-fold increase in CD8 + T cells and a 1.8-fold increase in regulatory T cells in the spleen. Splenic CD4 + and CD8 + T cells had increased expression of C-X-C Motif Chemokine Receptor 3 (CXCR3) and interferon- (IFN-), indicating a T helper 1 (Th1)-like/effector CD8 + T cell-like phenotype. Moreover, CBL-B deficient T cells had increased expression of programmed cell death protein 1 (PD-1) and T cell immunoreceptor with Ig and ITIM domains (TIGIT), indicating an exhausted T cell phenotype. In conclusion, CBL-B CD4cre Cbl-b cKO mice have reduced atherosclerosis, by inducing T cell exhaustion but show increased T cell accumulation in the plaque accompanied by systemic T cell activation.